Platelet size in myocardial infarction. - Cameron, H A (1983)
The mean platelet volume and platelet count were measured serially in 100 patients soon after myocardial infarction and again at a follow up clinic about seven weeks later. The results were compared with those in age matched controls. The mean platelet volume after infarction (mean 9.07 fl (SE 0.08] was significantly greater than in the controls (8.32 fl (SE 0.07); p less than 0.001), and was still raised at the follow up clinic (8.69 fl (SE 0.10); p less than 0.01). The mean platelet count on admission (275 X 10(9)/1 (SE 7] was significantly lower than in the control group (295 X 10(9)/1 (SE 5); p less than 0.05) and fell significantly during admission, with a mean change of -36 X 10(9)/1 (95% confidence limits -26, -45; p less than 0.01). At the follow up clinic the platelet count had risen to a level not significantly different from the admission value. As larger platelets are haemostatically more active, the finding of an increased mean platelet volume after myocardial infarction provides further evidence that abnormal platelet behaviour may be implicated in the process of infarction.